2021
DOI: 10.1016/j.talanta.2020.121726
|View full text |Cite
|
Sign up to set email alerts
|

Highly accurate and sensitive diagnostic detection of SARS-CoV-2 by digital PCR

Abstract: The outbreak of COVID-19 caused by a novel Coronavirus (termed SARS-CoV-2) has spread to over 210 countries around the world. Currently, reverse transcription quantitative qPCR (RT-qPCR) is used as the gold standard for diagnosis of SARS-CoV-2. However, the sensitivity of RT-qPCR assays of pharyngeal swab samples are reported to vary from 30% to 60%. More accurate and sensitive methods are urgently needed to support the quality assurance of the RT-qPCR or as an alternative diagnostic approach. A reverse transc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 16 publications
2
95
0
Order By: Relevance
“…ddPCR is also more sensitive for detecting low target copies and relatively insensitive to potential PCR inhibitors (198). Recent studies have reported higher sensitivity and robustness of ddPCR than RT-PCR for detection and quantification of SARS-CoV-2 RNA from purified RNA and crude lysate samples in UTM (196,199). Digital droplet assays which enable detection and quantification with limited sample processing could potentially be used for monitoring clinical course and convalescence (199).…”
Section: Other Methods Of Viral Rna Detectionmentioning
confidence: 99%
“…ddPCR is also more sensitive for detecting low target copies and relatively insensitive to potential PCR inhibitors (198). Recent studies have reported higher sensitivity and robustness of ddPCR than RT-PCR for detection and quantification of SARS-CoV-2 RNA from purified RNA and crude lysate samples in UTM (196,199). Digital droplet assays which enable detection and quantification with limited sample processing could potentially be used for monitoring clinical course and convalescence (199).…”
Section: Other Methods Of Viral Rna Detectionmentioning
confidence: 99%
“…Four commercially available, one customized from Pasteur Institute and in-house optimized RT-PCR protocols (description available in Table 1 ) 6 , 7 were compared. Primer probes design, reaction mix and thermal cycling conditions are shown in Table 2 , 3 and 4 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…No. 11732-088 Available upon request from Pasteur Institute In-house customized RT-PCR protocol Oncobit https://www.cdc.gov/coronavirus/2019-ncov/lab/rt-pcr-panel-primer-probes.html , September 7, 2020; 7 Ordered from Microsynth TaqPath 1-Step Multiplex Master Mix (no ROX) (A28521, ThermoFisher) SARS-CoV-2 Positive Run Control (#COV019CE) of Bio-Rad …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, dPCR showed higher sensitivity than RT‐qPCR in the testing of clinical samples. Some samples from patients with confirmed COVID‐19 were classified as positive by dPCR but found inconclusive or negative by RT‐qPCR 16,18–22 . For example, Suo et al 16 .…”
Section: Applications Of Digital Pcr In Covid‐19 Pandemicmentioning
confidence: 99%